Pengaruh Penggunaan Media Audio Visual Terhadap Minat Belajar Matematika Kelas IV SD Negeri 4 Karangkemojing - Alfisah, Vina Nur; Kurniawan, Alfi Muklis; Azizah, Amalia Nurul (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the effect of using audio-visual media on the learning interest in Mathematics of fourth-grade students at SD Negeri 4 Karangkemojing. The method used in this study is quantitative with a pre-experimental research type. The design used is a one-group pre-test and post-test, with data collection carried out using pre-test and post-test questionnaires. The average percentage of the post-test scores after the audio-visual media was applied to Mathematics learning is 85%. The results of the hypothesis test using the Paired Samples Test technique at a significance level of 5% obtained a t-value < 0.05, namely 0.004 < 0.05, thus Ho is rejected and Ha is accepted. From the results of this test, there is an effect of audiovisual media on the interest in learning mathematics in the fourth grade of SD Negeri 4 Karangkemojing